Deep Learning in teacher training: Experience with students of Education Teaching at the Universidad de Costa Rica (Innovaciones Educativas, 2020)
This paper presents a learning lab’s development from a critical reflection experience of the learning-teaching process within the classroom. The objective is to help teachers learn to create didactic strategies that establish a relation between the disciplinary content and students’ daily lives. Also, it urges teachers to ponder on their own teaching model and how it could change within a more significant process. This experience with students majored in Education and Teaching at Universidad de Costa Rica is based on the Deep Learning approach. For this reason, it uses critical reflection towards the change of paradigm through reading analyses, discussion forums, and the design of didactic strategies. The findings suggest teachers’ contribution regarding strategy creation for significant and enduring learning in the students’ lives is necessary. Also, it suggests the need to transcend superficial teaching towards deep learning and to transform the academy into a center of experience capitalization in order to know how to act in class, think for the class, and learning for teaching.
Keywords: Deep learning; critical thinking; pedagogical skills; teaching and training